Application of with C4.5 algorithm to measure the level of student satisfaction with student services - Sinaga, Bosker; Manurung, Jonson; Br Tarigan, Nera Mayana; Br Sitepu, Siska Feronika; Barus, Nadela (Politeknik Ganesha Medan, 2022)
In measuring the level of student satisfaction with student services, it is better to use a method/algorithm to find out how much in certain criteria/services the level of student satisfaction and which services need to be improved. In providing student services, it has been going well, but the difficulty in measuring the level of student satisfaction with student services has not used an algorithm. Data mining as a data mining technique is very important to use in extracting data from measurements that have been carried out so far. Data mining in analyzing data uses several algorithms, one of which is the C4.5 algorithm. The research method is the survey research method, which is a survey research method. This is a research method conducted using surveys or collecting data through research respondents. The purpose of this study is how to apply data mining with the C4.5 algorithm in measuring the level of student satisfaction with student services. This study targets the measurement results of academic criteria/services, guidance and counseling services, interest and talent services, scholarship services and health services. The results of this study were to determine the role of the decision tree on measuring the level of student satisfaction with student services.